A multifunctional covalent organic framework with localized radicals for selective ion capture and photocatalysis. (December 2022) - Zhao, W.; Sun, L.; Wang, B.; Yang, L.; Kang, X.; Sun, L.; Ren, G.; Fang, X.; Bai, T.; Deng, W-q.; Liu, C.
Abstract: Among various kinds of materials, covalent organic frameworks (COFs) are ideal candidates for targeting desired applications, as their conformations and topological structures can be precisely tuned by selection of appropriate building units and connection modes. Multifunctional COFs with integrated functions hold great promise for solving energy and environmental issues. A multifunctional COF (Por-BFBIm-COF) with dual active sites of imidazole ring and porphyrin was designed in this work. The Por-BFBIm-COF not only possessed the features of COFs such as crystallinity and porosity but also exhibited radical characteristics like high spin density (1.22E19 spin/g at 298 K). Selective ion capture, photocatalytic oxidative amine coupling, and photocatalytic α-terpinene oxidation were used as three model systems to demonstrate the capabilities of the Por-BFBIm-COF. In the presence of oxygen and visible light, the Por-BFBIm-COF exhibited very high activities in photocatalytic reactions with producing superoxide anion radical and singlet oxygen active species, respectively. The rational design of the multifunctional COF offered new insights for developing multifunctional materials in energy and environmental fields. Graphical abstract: Image 1 Here we report a multifunctional COF (Por-BFBIm-COF) with dual active sites of imidazole ring and porphyrin, which shows excellent performance in selective ion capture, photocatalytic oxidative amine coupling and photocatalytic α-terpinene oxidation. For photocatalytic reactions, mechanism studies show that the Por-BFBIm-COF could produce superoxide anion radical and singlet oxygen active species respectively in the presence of oxygen and visible light. Highlights: An ionic covalent organic framework with localized radicals is designed and synthesized. The COF exhibits excellent activity for selective ion capture and photocatalysis. O2 − and 1 O2 are produced as active species on the COF in the presence of oxygen and visible light.